AN EVALUATION STUDY OF PROSPECTIVE TEACHERS’ COMPETENCES IN TEACHING ELEMENTARY SCHOOL STUDENTS - Zahrina A. Hamid (SINTESA: Jurnal Kajian Islam dan Sosial Keagamaan, 2020)
This study evaluated competences of the students of Education for Islamic Primary Schools in real teaching or the program was renowned as PPL. The participants were 11 students which were named prospective teachers in this research, who spread out in three schools. The informants were the principals and the guide teachers.  The techniques of data collection employed observation, questionnaire and interview. The findings of the study were matched to the teacher’s competence standards. The findings revealed that the prospective teachers were excellent in personal and social criteria. They were also good at preparing teaching-learning equipments and supporting students’ talents. Nevertheless, they were weak in class organization. A few of them were difficult to face the different characters of the students. In addition, a few of them could not go smoothly with the teaching techniques used and were low at mastering the materials.